2011
DOI: 10.1007/s13258-010-0091-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure and polymorphisms of the 5′ regulatory region of porcine adenylate kinase 3-like 1 gene and effect on trait of meat quality

Abstract: The porcine adenylate kinase 3-like 1 (AK3L1) gene is considered as a potential candidate gene among the encoded isoforms of adenylate kinase for meat quality based on the functional role of the AK3L1 gene in energy metabolism via high-energy phosphoryl transfer reaction. The genomic position of the AK3L1 gene is located in the QTL region, which codes for traits of meat quality. We characterized the genomic structure of the porcine AK3L1 gene and found polymorphisms in the 5' regulatory region. Typical transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Previous studies have demonstrated that IMP is an effective flavor enhancer, approximately 50-fold more effective than monosodium glutamate (Yan et al, 2018). Hence, IMP is a useful indicator of meat flavor worldwide (Suzuki et al, 1994;Lee et al, 2011). In this experiment, 0.04% supplemental dietary CGA resulted in a significant increase in the content of IMP in the LD and BF muscles.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have demonstrated that IMP is an effective flavor enhancer, approximately 50-fold more effective than monosodium glutamate (Yan et al, 2018). Hence, IMP is a useful indicator of meat flavor worldwide (Suzuki et al, 1994;Lee et al, 2011). In this experiment, 0.04% supplemental dietary CGA resulted in a significant increase in the content of IMP in the LD and BF muscles.…”
Section: Discussionmentioning
confidence: 64%
“…This finding indicates that degradation of IMP and oxidization of Hx to Xt gradually increased with increasing storage days and that the umami taste and freshness of the chilled chicken meat gradually decreased. IMP thus has become an important index for measuring the umami taste of meat ( Lee et al., 2011 , Masic and Yeomans, 2014 ). According to the trends of IMP and other nucleotides observed, the highest possible shelf life of chilled chicken is 6 D. For best flavor, chilled chicken meat should be consumed within 4 D.
Figure 7 Relative changes of nucleosides and nucleotides in chilled chicken meat samples during chilled storage.
…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with a previous study that black-boned chickens showed higher level of IMP in muscle associated with excellent flavor and taste in meat [ 15 ]. IMP is a flavor enhancer that is 50 times more potent than monosodium glutamate and has been used internationally as an important index for measuring meat flavor [ 16 ]. Hypoxanthine is produced by the degradation of IMP during postmortem aging of meat.…”
Section: Discussionmentioning
confidence: 99%